Byzantine Beginnings: New Pedagogy for an Ancient Art - Hogg, Amy (Journal of the International Society for Orthodox Music, 2020)
In education, one must consider opportunity costs—if one thing is taught another thing cannot be. With Byzantine Beginnings I have focused on teaching the knowledge and skills necessary to learn to read heirmologic hymns (mostly syllabic hymns which tend to have the simplest rhythms and melodies). In most traditional reading methods, students learn all of the interval symbols and all of the rhythm symbols before they begin reading hymns. This is unnecessary. A good analogy can be found in the way children learn to read in English. After their phonemic awareness has developed and they have learned their letter sounds they learn to read CVC words (consonant-vowel-consonant) and some common sight words. Then they begin reading simple sentences. Students do not learn to read digraphs (ch, th, sh), the numerous ways that long vowels are represented (o_e, oa, ea) or r controlled vowels (ar, er, ir) before they begin reading simple sentences. If they were made to do this it would seem like a very long process with little payoff—as they would be unable to experience the joy of reading real books on their own. Some would argue that in traditional chant reading instruction students do read simple sentences, and at the surface level it appears so. The issue is that the melodic phrases found in traditional teaching methods are quite different than those found in Byzantine chant, and for this reason they do not have the real world connection and pay off that musical phrases from actual hymns do. The goal of Byzantine Beginnings is to give students the ear training, modal theory, and reading skills that will enable them to begin reading simple Byzantine chant hymns as quickly as possible. Byzantine Beginnings uses interactive games and manipulative materials that provides a multi-sensory approach, with visual, auditory, kinesthetic and spatial elements that make the learning process easier.